Potential‐Driven On/Off Switch Strategy for the Electrosynthesis of [7]Helicene‐Derived Polymers. Issue 12 (17th August 2017) - Hrbáč, Jan; Strašák, Tomáš; Fekete, Ladislav; Ladányi, Vít; Pokorný, Jan; Bulíř, Jiří; Krbal, Miloš; Žádný, Jaroslav; Storch, Jan; Vacek, Jan
Abstract: New materials bearing thiophene and helicene moieties were prepared by using a potential‐driven on/off switch strategy on the surface of glassy carbon and indium tin oxide substrates. Specifically, a 3‐([7]helicen‐9‐yl)‐thiophene hybrid monomer was electrooxidized in acetonitrile by using cyclic voltammetry with anodic potential limits of +1.5 or +2.5 V, resulting in a conductive and non‐conductive polymer, respectively. The electrochemical findings were supplemented by microscopy investigations, UV/Vis, fluorescence and vibrational spectroscopies, and 1 H NMR spectroscopy as well as ellipsometry measurements and computational chemistry. The electrodeposited polymers could be used for the further development of materials applicable in organic electronics, optoelectronics, and sensing technologies. Abstract : A joint effort : Polymers based on [7]helicene and thiophene are prepared. Conductive and non‐conductive thin layers are synthesized electrochemically. Carbon and indium tin oxide substrates are used for polymer deposition. A joint experimental and computational approach is applied.